Market potential analysis of canned pineapple in major importing countries - Matuguina, Marlon G.; Digal, Larry N.
Pineapple has been one of the major fruit exports of the Philippines. These exports of pineapples have diversified into three major forms such as the fresh pineapple, canned pineapple and pineapple juices. Aside from the dollar earnings it brings to the country, this industry is also very important in the employment generation in the country. Many farmers and agricultural sector are becoming independent in this industry, most especially in the Northern Mindanao regions. This paper examined the market potential of Philippines' canned pineapple in its major importing countries to examine the likelihood of market expansions. The researcher used secondary time-series data in constructing the demand models of canned pineapple in the export market. Ordinary Least Square (OLS) and simultaneous equations using Seemingly Unrelated Regression (SUR) were used in the import demand estimations. The result was able to identify the Ordinary Least Square (OLS) applied in this study was already fully efficient and there was no need for Seemingly Unrelated Regression estimation. Moreover, the study was able to identify that Philippine canned pineapple is a normal good in Japan and Netherlands which suggest that canned pineapple has market potential in these countries. Thus, there are still opportunities for market expansions in Japan and Netherlands. For the industry to remain competitive in the export market, the government must provide support mechanisms, implement price reduction policies and invest in the processing industry. The private sector must also set pricing strategies in the different export markets to take advantage on consumers' responsiveness to change in price.
Thesis, Undergraduate (BS Agribusiness Economics)--University of Philippines, Mindanao